Slag composition, slag material and preparation method thereof
By adding calcium carbide slag, sodium carbonate and polyepoxy sodium succinate to the alkali-excited slag material, the problems of slow development of strength and poor fluidity in the early stage were solved, and the preparation of slag material with high flow and early compressive strength was achieved.
Patent Information
- Application Number
- CN202510038972.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The existing alkali-activated slag materials have disadvantages in terms of slow early strength development and poor liquidity, and have high energy consumption in the production process and large emissions of polluted gases.
High flow sodium carbonate excitation slurry is prepared by adding calcium carbide slag, sodium carbonate and specific admixtures, such as polyepoxy-succinate, to the slag composition.
The early strength development and fluidity of sodium carbonate stimulated slag is significantly improved, and slag materials with high flow and acceptable early compressive strength are prepared.
Smart Images

Figure BDA0005236378760000111 
Figure BDA0005236378760000121 
Figure HDA0005236379090000011
Abstract
Description
Technical Field
[0001] The present application relates to the field of solid waste resource utilization, and in particular to a slag composition, a slag material and a preparation method thereof. Background Art
[0002] Compared with silicate cement, alkali-activated slag has the advantages of high early strength, good high temperature resistance, acid and alkali corrosion resistance, etc. Because it is mainly composed of granulated blast furnace slag, which is industrial waste, it also shows good economy and environmental protection. At present, the mainstream alkali-activated slag materials mostly use sodium silicate and sodium hydroxide as alkaline activators to dissociate granulated blast furnace slag and dissolve it to produce a large number of active ions. However, sodium silicate and sodium hydroxide have the disadvantages of high cost, high corrosiveness, high viscosity, etc., and the production process is generally accompanied by a large amount of energy consumption and emission of polluting gases.
[0003] Compared with sodium silicate and sodium hydroxide, sodium carbonate can be directly extracted from natural alkali at a lower cost. Its own pH buffering capacity also improves the safety of operators during the preparation of alkali slag. Therefore, the use of sodium carbonate as an alkaline activator for granulated blast furnace slag has many advantages. However, sodium carbonate alkali-activated slag also has some problems, such as slow early strength development and poor fluidity. Summary of the invention
[0004] In view of the above problems in the prior art, the present application provides a slag composition, a slag material and a preparation method thereof.
[0005] In a first aspect, the present application provides a slag composition, which includes slag, carbide slag, sodium carbonate and an admixture, wherein the admixture includes sodium polyepoxysuccinate.
[0006] The slag composition of the present application can significantly improve the shortcomings of sodium carbonate alkali activated slag such as slow early strength development and poor fluidity by using carbide slag powder and specific additives. The slag composition of the present application can be used to prepare a high fluidity sodium carbonate activated slag slurry.
[0007] In some embodiments, the additive further comprises one or more of polymaleic anhydride, sodium tungstate and sodium phosphate.
[0008] In some embodiments, the additive is sodium polyepoxysuccinate.
[0009] In some embodiments, the additives are sodium polyepoxysuccinate and sodium tungstate.
[0010] In some embodiments, the additive is sodium polyepoxysuccinate, sodium tungstate and sodium phosphate.
[0011] In some embodiments, the additive is sodium polyepoxysuccinate, polymaleic anhydride, sodium tungstate and sodium phosphate.
[0012] In some embodiments, based on the total mass of slag and carbide slag, the mass content of the admixture is 0.05%-0.6%, for example, 0.07%, 0.09%, 0.1%, 0.11%, 0.13%, 0.15%, 0.17%, 0.19%, 0.2%, 0.21%, 0.23%, 0.25%, 0.27%, 0.29%, 0.3%, 0.31%, 0.33%, 0.35%, 0.37%, 0.39%, 0.4%, 0.41%, 0.43%, 0.45%, 0.47%, 0.59%, 0.5%, 0.51%, 0.53%, 0.55%, 0.57%, 0.59% or any value therebetween. In some embodiments, the mass content of the admixture is 0.1%-0.5%. In some embodiments, the mass content of the additive is 0.2%-0.4%.
[0013] In some embodiments, based on the mass of the admixture, the mass content of the sodium polyepoxysuccinate is 70%-100%, for example, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or any value therebetween. In some embodiments, the mass content of the sodium polyepoxysuccinate is 80%-100%.
[0014] In some embodiments, based on the total mass of slag and carbide slag, the mass content of sodium carbonate is 2%-12%, for example, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5% or any value therebetween. In some embodiments, the mass content of sodium carbonate is 4%-10%.
[0015] In some embodiments, the slag composition does not include other alkali activators besides sodium carbonate.
[0016] In some embodiments, based on the total mass of slag and carbide slag, the mass content of carbide slag is 1%-10%, for example, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or any value of their mass. In some embodiments, the mass content of carbide slag is 3%-8%.
[0017] In some embodiments, the specific surface area of the slag is greater than or equal to 400 m 2 / kg, for example 400m 2 / kg-600m 2 In some embodiments, the specific surface area of the slag is 430m 2 / kg, 450m 2 / kg, 470m 2 / kg、500m 2 / kg, 530m 2 / kg, 550m 2 / kg or 570m 2 / kg.
[0018] In some embodiments, the 28d activity index of the slag is greater than or equal to 95% (tested according to GB / T 18046-2017), for example, 95%-110%. In some embodiments, the 28d activity index of the slag is 96%, 97%, 98%, 99%, 100%, 101%, 102%, 103%, 104%, 105%, 106%, 107%, 108% or 109%.
[0019] In some embodiments, the specific surface area of the carbide slag should be greater than or equal to 300m 2 / kg, for example, 300m 2 / kg-500m 2 In some embodiments, the specific surface area of the carbide slag is 330m 2 / kg、350m 2 / kg, 370m 2 / kg、400m 2 / kg, 430m 2 / kg, 450m 2 / kg or 470m 2 / kg.
[0020] In some embodiments, the effective calcium hydroxide content in the carbide slag is greater than or equal to 70%, for example, 70%-90%. In some embodiments, the effective calcium hydroxide content in the carbide slag is 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88% or 89%.
[0021] In a second aspect, the present application provides a slag material, which includes the slag composition described in the first aspect and water.
[0022] In some embodiments, the mass ratio of water to slag composition (water-to-solid ratio) is 0.30-0.50, for example, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48 or 0.49. In some embodiments, the mass ratio of water to slag composition is 0.40-0.45.
[0023] The slag material provided by the present application has high fluidity and acceptable early compressive strength after the slurry is hardened.
[0024] In a third aspect, the present application provides a method for preparing the slag material according to the second aspect (delayed addition), which comprises the following steps:
[0025] A1: Mixing an admixture or a solution containing an admixture with a portion of water to obtain an admixture mixed solution;
[0026] A2: mixing the sodium carbonate, slag and carbide slag with the remaining water for a first time t1 to obtain a first mixed solution;
[0027] A3: After the first mixed liquid is allowed to stand for a second time t2, the admixture mixed liquid and the first mixed liquid are mixed for a second time to obtain the slag material.
[0028] In some embodiments, in step A1, the portion of water is 10%-30% of the total mass of water, for example, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29% or any value therebetween.
[0029] In some embodiments, in step A2, the first mixing includes first low-speed mixing and first high-speed mixing performed sequentially.
[0030] In some embodiments, the rotation speed of the first low-speed mixing is 100 r / min-200 r / min, for example, 110 r / min, 130 r / min, 150 r / min, 170 r / min or 190 r / min.
[0031] In some embodiments, the rotation speed of the first high-speed mixing is 250 r / min-500 r / min, for example, 270 r / min, 290 r / min, 300 r / min, 310 r / min, 330 r / min, 350 r / min, 370 r / min, 390 r / min, 400 r / min, 410 r / min, 430 r / min, 450 r / min, 470 r / min or 490 r / min.
[0032] In some embodiments, 0.06≤t2 / t1≤15, for example, t2 / t1 is 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12, 12.5, 13, 13.5, 14, 14.5 or any value therebetween.
[0033] In some embodiments, 2 min≤t2≤10 min, for example, t2 is 2 min, 2.5 min, 3 min, 3.5 min, 4 min, 4.5 min, 5 min, 5.5 min, 6 min, 6.5 min, 7 min, 7.5 min, 8 min, 8.5 min, 9 min, 9.5 min or any value therebetween.
[0034] In some embodiments, 0.5 min≤t1≤30 min, for example, t1 is 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 13 min, 15 min, 17 min, 19 min, 20 min, 21 min, 23 min, 25 min, 27 min, 29 min or any value therebetween.
[0035] In some embodiments, the rotation speed time of the first low-speed mixing is 1 min-15 min, for example, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 13 min or any value therebetween.
[0036] In some embodiments, the speed time of the first high-speed mixing is 1 min-15 min, for example, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 13 min or any value therebetween.
[0037] In some embodiments, in step A3, the second mixing includes a second low-speed mixing and a second high-speed mixing performed sequentially.
[0038] In some embodiments, the rotation speed of the second low-speed mixing is 100 r / min-200 r / min, for example, 110 r / min, 130 r / min, 150 r / min, 170 r / min or 190 r / min.
[0039] In some embodiments, the rotation speed of the second high-speed mixing is 250 r / min-500 r / min, for example, 270 r / min, 290 r / min, 300 r / min, 310 r / min, 330 r / min, 350 r / min, 370 r / min, 390 r / min, 400 r / min, 410 r / min, 430 r / min, 450 r / min, 470 r / min or 490 r / min.
[0040] In some embodiments, the second mixing time is 0.5 min-10 min, for example, 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min or 9 min.
[0041] In some embodiments, the second low-speed mixing time is 0.5 min-10 min, for example, 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min or 9 min.
[0042] In some embodiments, the second high-speed mixing time is 0.5 min-10 min, for example, 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min or 9 min.
[0043] In some embodiments, the mass concentration of the admixture in the solution containing the admixture is greater than or equal to 40%, such as 40%-50%. In some embodiments, the mass concentration of the admixture is 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48% or 49%.
[0044] In some embodiments, the solution of the admixture is selected from an aqueous solution of the admixture.
[0045] In some embodiments, the solution containing the additive is a sodium polyepoxysuccinate solution with a concentration of ≥40%. In some embodiments, the density of the sodium polyepoxysuccinate solution is 1.25-1.30 g / cm 3 In some embodiments, the pH value of the 1% solution of the sodium polyepoxysuccinate solution is 9.0-12.0.
[0046] In some embodiments, the solution containing the additive is a polymaleic anhydride solution with a concentration of ≥40%. In some embodiments, the density of the polymaleic anhydride solution is 1.19-1.22 g / cm 3 .
[0047] In some embodiments, the preparation method comprises the following specific steps:
[0048] The admixture or admixture solution (such as sodium polyepoxysuccinate solution, polymaleic anhydride solution, sodium tungstate or sodium phosphate) is first mixed with 10%-30% of water to obtain a standby solution. The powder (sodium carbonate, slag and carbide slag) is first stirred with the remaining 70%-90% of water to obtain an initial slurry.
[0049] The timing starts from the moment when the powder contacts the water. After a time t min (2<t<10), the reserved solution is added to the initial slurry obtained above, and stirring is continued to obtain a high-fluidity sodium carbonate-activated slag slurry.
[0050] In a fourth aspect, the present application provides a method for preparing the slag material according to the second aspect (immediate addition), comprising the following steps:
[0051] B1: mixing an admixture or a solution containing an admixture with water to obtain an admixture mixed solution;
[0052] B2: The admixture mixture is mixed with sodium carbonate, slag and carbide slag for a third time to obtain the slag material.
[0053] In some embodiments, in step B2, the third mixing includes third low-speed mixing and third high-speed mixing performed sequentially.
[0054] In some embodiments, the rotation speed of the third low-speed mixing is 100 r / min-200 r / min, for example, 110 r / min, 130 r / min, 150 r / min, 170 r / min or 190 r / min.
[0055] In some embodiments, the rotation speed of the third high-speed mixing is 250r / min-500r / min, for example, 270r / min, 290r / min, 300r / min, 310r / min, 330r / min, 350r / min, 370r / min, 390r / min, 400r / min, 410r / min, 430r / min, 450r / min, 470r / min or 490r / min.
[0056] In some embodiments, the third mixing time is 0.5 min-10 min, for example, 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min or 9 min.
[0057] In some embodiments, the third low-speed mixing time is 0.5 min-10 min, for example, 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min or 9 min.
[0058] In some embodiments, the third high-speed mixing time is 0.5 min-10 min, for example, 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min or 9 min.
[0059] In some embodiments, the mass concentration of the admixture in the solution containing the admixture is greater than or equal to 40%, such as 40%-50%. In some embodiments, the mass concentration of the admixture is 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48% or 49%.
[0060] In some embodiments, the solution of the admixture is selected from an aqueous solution of the admixture.
[0061] In some embodiments, the solution containing the additive is a sodium polyepoxysuccinate solution with a concentration of ≥40%. In some embodiments, the density of the sodium polyepoxysuccinate solution is 1.25-1.30 g / cm 3 In some embodiments, the pH value of the 1% solution of the sodium polyepoxysuccinate solution is 9.0-12.0.
[0062] In some embodiments, the solution containing the additive is a polymaleic anhydride solution with a concentration of ≥40%. In some embodiments, the density of the polymaleic anhydride solution is 1.19-1.22 g / cm 3 .
[0063] In some embodiments, the preparation method comprises the following specific steps:
[0064] Add an admixture or an admixture solution (such as sodium polyepoxysuccinate solution, polymaleic anhydride solution, sodium tungstate or sodium phosphate) directly into the powder, and obtain a high-fluidity sodium carbonate-activated slag slurry after stirring.
[0065] The sodium carbonate activated slag slurry provided in the present application has high fluidity and acceptable early compressive strength after the slurry hardens. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] In order to more clearly illustrate the embodiments of the present invention or the solutions in the prior art, the following is a brief introduction to the drawings required for use in the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0067] Figure 1 The variation trend of the slurry fluidity of Examples 1-5 and Comparative Examples 1-2 with the dosage of the admixture is shown.
[0068] Figure 2 The variation trend of the slurry fluidity of Examples 6-10 and Comparative Examples 1-2 with the dosage of the admixture is shown. DETAILED DESCRIPTION
[0069] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments and drawings. The specific embodiments described herein are only used to explain the present application and are not intended to constitute any limitation to the present application.
[0070] In the following examples and comparative examples, "%" represents mass percentage unless otherwise specified.
[0071] In the following embodiments and comparative examples, the water-to-solid ratio refers to the mass ratio of water to the total mass of the slag composition (the total mass of sodium carbonate, carbide slag powder, slag powder and admixtures).
[0072] In the following examples and comparative examples, the specific surface area of the carbide slag powder is 350 m 2 / kg, effective calcium hydroxide content is 76%.
[0073] In the following examples and comparative examples, the specific surface area of slag powder should be 420m 2 / kg, and the activity index at 28 days was 103%.
[0074] In the following examples and comparative examples, the concentration of the polyepoxy sodium succinate solution (PESA solution) is 40%, Shandong Yousuo Chemical Technology Co., Ltd.
[0075] In the following examples and comparative examples, the concentration of the polymaleic anhydride solution (HPMA solution) is 40%, Shandong Yousuo Chemical Technology Co., Ltd.
[0076] In the following examples and comparative examples, the flow diameter of the slurry was tested using a hollow truncated cone of 36 mm×60 mm×60 mm.
[0077] Specifically, after the final slurry obtained by stirring fills the hollow truncated cone, lift the truncated cone vertically to allow the slurry to flow freely on a smooth glass plate, and then measure the diameters in two perpendicular directions, and take the average value as the flow diameter of the slurry. Before the 20min and 60min slurry flowability tests, the slurry needs to be quickly stirred for 1min before testing.
[0078] In the following embodiments and comparative examples, the rotation speed of slow stirring is 140 r / min, and the rotation speed of fast stirring is 285 r / min.
[0079] The present application is further described below in conjunction with specific embodiments and comparative examples.
[0080] Example 1
[0081] Set the experimental water-to-solid ratio to 0.45. Weigh 25.65g of sodium carbonate powder, 146.54g of water, 15g of carbide slag powder, 285g of slag powder, and 0.75g of PESA solution (0.3g of PESA). Dissolve PESA in 146.54g of water, mix with all the powders and stir slowly for 2 minutes, then stir quickly for 2 minutes to obtain the final slurry.
[0082] The initial fluidity of the slurry is 135 mm, the fluidity after 20 minutes is 105 mm, and the fluidity after 60 minutes is 90 mm.
[0083] Example 2
[0084] Set the experimental water-solid ratio to 0.45. Weigh 25.65g of sodium carbonate powder, 146.54g of water, 15g of carbide slag powder, 285g of slag powder, and 1.5g of PESA solution (0.6g of PESA). Dissolve PESA in 146.54g of water, mix with all the powders and stir slowly for 2 minutes, then stir quickly for 2 minutes to obtain the final slurry.
[0085] The initial fluidity of the slurry is 144 mm, the fluidity at 20 min is 117 mm, and the fluidity at 60 min is 91.5 mm.
[0086] Example 3
[0087] Set the experimental water-solid ratio to 0.45. Weigh 25.65g of sodium carbonate powder, 146.54g of water, 285g of slag powder, 15g of carbide slag powder, and 2.25g of PESA solution (0.9g of PESA). Dissolve PESA in 146.54g of water, mix with all the powders and stir slowly for 2 minutes, then stir quickly for 2 minutes to obtain the final slurry.
[0088] The initial fluidity of the slurry is 150 mm, the fluidity after 20 minutes is 130 mm, and the fluidity after 60 minutes is 92.5 mm.
[0089] Example 4
[0090] Set the experimental water-solid ratio to 0.45. Weigh 25.65g of sodium carbonate powder, 146.54g of water, 285g of slag powder, 15g of carbide slag powder, and 3g of PESA solution (1.2g of PESA). Dissolve PESA in 146.54g of water, mix with all the powders and stir slowly for 2 minutes, then stir quickly for 2 minutes to obtain the final slurry.
[0091] The initial fluidity of the slurry is 155.5 mm, the fluidity at 20 min is 179 mm, and the fluidity at 60 min is 105 mm.
[0092] Example 5
[0093] Set the experimental water-solid ratio to 0.45. Weigh 25.65g of sodium carbonate powder, 146.54g of water, 285g of slag powder, 15g of carbide slag powder, and 3.75g of PESA solution (1.5g of PESA). Dissolve PESA in 146.54g of water, mix with all the powders and stir slowly for 2 minutes, then stir quickly for 2 minutes to obtain the final slurry.
[0094] The initial fluidity of the slurry is 160mm, the fluidity after 20 minutes is 187mm, and the fluidity after 60 minutes is 120mm (water seepage occurs, and the water and particles in the slurry are separated into layers).
[0095] Example 6
[0096] Set the experimental water-to-solid ratio to 0.45. Weigh 25.65g of sodium carbonate powder, 146.54g of water, 285g of slag powder, 15g of carbide slag powder, and 0.75g of PESA solution (0.3g of PESA). Dissolve PESA in 21.98g of water for later use. Mix 124.56g of water with all other powders and stir slowly for 1min, then stir quickly for 1min to obtain the initial slurry. Then wait for 3min (t=5min, 5-2(stirring time)=3min), add the reserved solution to the initial slurry, stir slowly for 1min, and then stir quickly for 1min to obtain the final slurry.
[0097] The initial fluidity of the slurry is 150 mm, the fluidity after 20 minutes is 160 mm, and the fluidity after 60 minutes is 145 mm.
[0098] Example 7
[0099] Set the experimental water-to-solid ratio to 0.45. Weigh 25.65g of sodium carbonate powder, 146.54g of water, 285g of slag powder, 15g of carbide slag powder, and 1.5g of PESA solution (0.6g of PESA). Dissolve PESA in 21.98g of water for later use. Mix 124.56g of water with all other powders and stir slowly for 1min, then stir quickly for 1min to obtain the initial slurry. Then wait for 3min (t=5min, 5-2(stirring time)=3min), add the reserved solution to the initial slurry, stir slowly for 1min, and then stir quickly for 1min to obtain the final slurry.
[0100] The initial fluidity of the slurry is 165 mm, the fluidity after 20 minutes is 190 mm, and the fluidity after 60 minutes is 180 mm.
[0101] Example 8
[0102] Set the experimental water-to-solid ratio to 0.45. Weigh 25.65g of sodium carbonate powder, 146.54g of water, 285g of slag powder, 15g of carbide slag powder, and 2.25g of PESA solution (0.9g of PESA). Dissolve PESA in 21.98g of water for later use. Mix 124.56g of water with all other powders and stir slowly for 1min, then stir quickly for 1min to obtain the initial slurry. Then wait for 3min (t=5min, 5-2(stirring time)=3min), add the reserved solution to the initial slurry, stir slowly for 1min, and then stir quickly for 1min to obtain the final slurry.
[0103] The initial fluidity of the slurry is 175 mm, the fluidity after 20 minutes is 200 mm, and the fluidity after 60 minutes is 205 mm.
[0104] Example 9
[0105] Set the experimental water-to-solid ratio to 0.45. Weigh 25.65g of sodium carbonate powder, 146.54g of water, 285g of slag powder, 15g of carbide slag powder, and 3g of PESA solution (1.2g of PESA). Dissolve PESA in 21.98g of water for later use. Mix 124.56g of water with all other powders and stir slowly for 1min, then stir quickly for 1min to obtain the initial slurry. Then wait for 3min (t=5min, 5-2 (stirring time)=3min), add the reserved solution to the initial slurry, stir slowly for 1min, and then stir quickly for 1min to obtain the final slurry.
[0106] The initial fluidity of the slurry is 200mm, the fluidity after 20 minutes is 200mm, and the fluidity after 60 minutes is 205mm (water seepage occurs, and the water and particles in the slurry are separated into layers).
[0107] Example 10
[0108] Set the experimental water-to-solid ratio to 0.45. Weigh 25.65g of sodium carbonate powder, 146.54g of water, 285g of slag powder, 15g of carbide slag powder, and 3.75g of PESA solution (1.5g of PESA). Dissolve PESA in 21.98g of water for later use. Mix 124.56g of water with all other powders and stir slowly for 1min, then stir quickly for 1min to obtain the initial slurry. Then wait for 3min (t=5min, 5-2 (stirring time)=3min), add the reserved solution to the initial slurry, stir slowly for 1min, and then stir quickly for 1min to obtain the final slurry.
[0109] The initial fluidity of the slurry was 208 mm, the fluidity after 20 minutes was 204 mm, and the fluidity after 60 minutes was 205 mm (water seepage occurred, and the water and particles in the slurry were separated into layers).
[0110] Embodiment 11
[0111] Set the experimental water-to-solid ratio to 0.45. Weigh 25.65g of sodium carbonate powder, 146.54g of water, 285g of slag powder, 15g of carbide slag powder, 1.3g of PESA solution (0.52g of PESA), and 0.08g of sodium tungstate powder. Dissolve PESA and sodium tungstate powder in 21.98g of water for later use. Mix 124.56g of water with all other powders and stir slowly for 1min, then stir quickly for 1min to obtain the initial slurry. Then wait for 3min (t=5min, 5-2 (stirring time)=3min), add the reserved solution to the initial slurry, stir slowly for 1min, and then stir quickly for 1min to obtain the final slurry.
[0112] The initial fluidity of the slurry is 170 mm, the fluidity after 20 minutes is 180 mm, and the fluidity after 60 minutes is 185 mm.
[0113] Example 12
[0114] Set the experimental water-solid ratio to 0.45, weigh 25.65g sodium carbonate powder, 146.54g water, 285g slag powder, 15g carbide slag powder, 1.3g PESA solution (0.52g PESA), 0.06g sodium tungstate powder, and 0.02g sodium phosphate powder. Dissolve PESA, sodium tungstate, and sodium phosphate powders in 21.98g water for later use. Mix 124.56g water with all other powders and stir slowly for 1min, then stir quickly for 1min to obtain the initial slurry. Then wait for 3min (t=5min, 5-2 (stirring time)=3min), add the standby solution to the initial slurry, stir slowly for 1min, and then stir quickly for 1min to obtain the final slurry.
[0115] The initial fluidity of the slurry is 174 mm, the fluidity at 20 minutes is 179 mm, and the fluidity at 60 minutes is 175 mm.
[0116] Example 13
[0117] Set the experimental water-to-solid ratio to 0.42. Weigh 25.65g of sodium carbonate powder, 146.54g of water, 285g of slag powder, 15g of carbide slag powder, 1.3g of PESA solution (0.52g of PESA), 0.1g of HPMA solution (0.04g of HPMA), and 0.04g of sodium tungstate powder. Dissolve PESA, HPMA, and sodium tungstate powder in 21.98g of water for later use. Mix 124.56g of water with all other powders and stir slowly for 1min, then stir rapidly for 1min to obtain an initial slurry. Then wait for 3min (t=5min, 5-2 (stirring time)=3min), add the standby solution to the initial slurry, stir slowly for 1min, and then stir rapidly for 1min to obtain the final slurry.
[0118] The initial fluidity of the slurry is 180 mm, the fluidity after 20 minutes is 180 mm, and the fluidity after 60 minutes is 175 mm.
[0119] Embodiment 14
[0120] Set the experimental water-solid ratio to 0.42, weigh 25.65g sodium carbonate powder, 146.54g water, 285g slag powder, 15g carbide slag powder, 1.3g PESA solution (0.52g PESA), 0.1g HPMA solution (0.04g HPMA), 0.03g sodium tungstate powder, and 0.01g sodium phosphate powder. Dissolve PESA, HPMA, sodium tungstate powder, and sodium phosphate powder in 21.98g water for later use. Mix 124.56g water with all other powders and stir slowly for 1min, then stir quickly for 1min to obtain the initial slurry. Then wait for 3min (t=5min, 5-2 (stirring time)=3min), add the standby solution to the initial slurry, stir slowly for 1min, and then stir quickly for 1min to obtain the final slurry.
[0121] The initial fluidity of the slurry is 180 mm, the fluidity after 20 minutes is 185 mm, and the fluidity after 60 minutes is 180 mm.
[0122] Embodiment 15
[0123] Set the experimental water-to-solid ratio to 0.42. Weigh 25.65g of sodium carbonate powder, 136.77g of water, 285g of slag powder, 15g of carbide slag powder, 1.95g of PESA solution (0.78g of PESA), and 0.12g of sodium tungstate powder. Dissolve PESA and sodium tungstate powder in 20.52g of water for later use. Mix 116.25g of water with all other powders and stir slowly for 1min, then stir quickly for 1min to obtain the initial slurry. Then wait for 3min (t=5min, 5-2 (stirring time)=3min), add the standby solution to the initial slurry, stir slowly for 1min, and then stir quickly for 1min to obtain the final slurry.
[0124] The initial fluidity of the slurry is 180 mm, the fluidity after 20 minutes is 192 mm, and the fluidity after 60 minutes is 185 mm.
[0125] Example 16
[0126] Set the experimental water-to-solid ratio to 0.42. Weigh 25.65g sodium carbonate powder, 136.77g water, 285g slag powder, 15g carbide slag powder, 1.95g PESA solution (0.78g PESA), 0.09g sodium tungstate powder, and 0.03g sodium phosphate powder. Dissolve PESA in 20.52g water for later use. Mix 116.25g water with all other powders and stir slowly for 1min, then stir quickly for 1min to obtain the initial slurry. Then wait for 3min (t=5min, 5-2 (stirring time)=3min), add the reserve solution to the initial slurry, stir slowly for 1min, and then stir quickly for 1min to obtain the final slurry.
[0127] The initial fluidity of the slurry is 184 mm, the fluidity after 20 minutes is 188 mm, and the fluidity after 60 minutes is 180 mm.
[0128] Comparative Example 1
[0129] Set the experimental water-to-solid ratio to 0.45. Weigh 25.65 g of sodium carbonate powder, 146.54 g of water, and 300 g of slag powder. Mix all the powders with 146.54 g of water and stir slowly for 2 minutes, then stir quickly for 2 minutes to obtain the final slurry.
[0130] The initial fluidity of the slurry is 120 mm, the fluidity after 20 minutes is 105 mm, and the fluidity after 60 minutes is 80 mm.
[0131] Comparative Example 2
[0132] Set the experimental water-to-solid ratio to 0.45. Weigh 25.65g of sodium carbonate powder, 146.54g of water, 15g of carbide slag powder, and 285g of slag powder. Mix all the powders with 146.54g of water and stir slowly for 2 minutes, then stir quickly for 2 minutes to obtain the final slurry.
[0133] The initial fluidity of the slurry is 110 mm, the fluidity after 20 minutes is 98 mm, and the fluidity after 60 minutes is 80 mm.
[0134] The test results of the raw material amounts and slurry fluidity of the above embodiments and comparative examples are shown in Table 1 and Figure 1-2 .
[0135] Table 1
[0136]
[0137] Note: Examples 1-5 use an immediate addition method to add the admixture, while Examples 6-16 use a delayed addition method to add the admixture.
[0138] From Table 1 and Figure 1-2 It can be seen from the data that compared with the comparative example, the sodium carbonate activated slag slurry prepared in the present application has higher fluidity.
[0139] In addition to the improved flowability, taking some embodiments as examples, the variation trend of immediate addition (direct addition) and delayed addition with the admixture dosage conforms to the equation provided in the following table, and the specific equation parameters are shown in Table 2. Compared with the comparative examples, the fluidity of the embodiments is significantly improved.
[0140] Table 2
[0141]
[0142] The technical solution of the present application is not limited to the above-mentioned specific embodiments, and all technical variations made according to the technical solution of the present application fall within the protection scope of the present application.
Claims
1. A slag composition comprising slag, carbide slag, sodium carbonate and an admixture, wherein the admixture comprises sodium polyepoxysuccinate.
2. The slag composition according to claim 1, characterized in that The additive also includes one or more of polymaleic anhydride, sodium tungstate and sodium phosphate; Preferably, the additive is sodium polyepoxysuccinate; Preferably, the additives are sodium polyepoxysuccinate and sodium tungstate; Preferably, the additive is sodium polyepoxysuccinate, sodium tungstate and sodium phosphate; Preferably, the additive is sodium polyepoxysuccinate, polymaleic anhydride, sodium tungstate and sodium phosphate.
3. The slag composition according to claim 1 or 2, characterized in that: Based on the total mass of slag and carbide slag, the mass content of the admixture is 0.05%-0.6%, preferably 0.1%-0.5%, more preferably 0.2%-0.4%; and / or Based on the mass of the admixture, the mass content of the sodium polyepoxysuccinate is 70%-100%, preferably 80%-100%.
4. The slag composition according to any one of claims 1 to 3, characterized in that Based on the total mass of slag and carbide slag, the mass content of sodium carbonate is 2%-12%, preferably 4%-10%; and / or Based on the total mass of slag and carbide slag, the mass content of carbide slag is 1%-10%, preferably 3%-8%.
5. The slag composition according to any one of claims 1 to 4, characterized in that The specific surface area of the slag is greater than or equal to 400m 2 / kg, for example 400m 2 / kg-600m 2 / kg, the 28d activity index of the slag is greater than or equal to 95%, for example, 95%-110%; and / or The specific surface area of the carbide slag should be greater than or equal to 300m 2 / kg, for example, 300m 2 / kg-500m 2 / kg, the effective calcium hydroxide content in the carbide slag is greater than or equal to 70%, for example, 70%-90%.
6. A slag material comprising the slag composition according to any one of claims 1 to 5 and water, Preferably, the mass ratio of water to slag composition is 0.30-0.50, preferably 0.40-0.
45.
7. A method for preparing the slag material according to claim 6, comprising the following steps: A1: Mixing an admixture or a solution containing an admixture with a portion of water to obtain an admixture mixed solution; A2: mixing the sodium carbonate, slag and carbide slag with the remaining water for a first time t1 to obtain a first mixed solution; A3: After the first mixed liquid is allowed to stand for a second time t2, the admixture mixed liquid and the first mixed liquid are mixed for a second time to obtain the slag material.
8. A method for preparing the slag material according to claim 6, comprising the following steps: B1: mixing an admixture or a solution containing an admixture with water to obtain an admixture mixed solution; B2: The admixture mixture is mixed with sodium carbonate, slag and carbide slag for a third time to obtain the slag material.
9. The preparation method according to claim 7 or 8, characterized in that: In step A1, the partial water is 10%-30% of the total mass of the water; and / or In step A2, the first mixing includes a first low-speed mixing and a first high-speed mixing performed sequentially, preferably, the rotation speed of the first low-speed mixing is 100r / min-200r / min, and the rotation speed of the first high-speed mixing is 250r / min-500r / min; and / or 0.06≤t2 / t1≤15, preferably, 2min≤t2≤10min, 0.5min≤t1≤30min; In step A3, the second mixing includes a second low-speed mixing and a second high-speed mixing performed sequentially, preferably, the rotation speed of the second low-speed mixing is 100r / min-200r / min, and the rotation speed of the second high-speed mixing is 250r / min-500r / min; and / or In step B2, the third mixing includes a third low-speed mixing and a third high-speed mixing performed sequentially. Preferably, the rotation speed of the third low-speed mixing is 100 r / min-200 r / min, and the rotation speed of the third high-speed mixing is 250 r / min-500 r / min.
10. The preparation method according to any one of claims 7 to 9, characterized in that: The mass concentration of the admixture in the solution containing the admixture is greater than or equal to 40%, such as 40%-50%; and / or The solution of the additive is selected from aqueous solutions of additives.
Citation Information
Patent Citations
Cement grinding aid taking industrial residue as raw material and preparation method of cement grinding aid
CN104529223A
Chloride-free enhanced slump-retaining cement grinding aid and preparation method thereof
CN109081629A
Alkali-activated gelling composition, slag material and application thereof
CN118637844A
Slag filling material and application thereof
CN119100672A
Concrete compositions using blast-furnace slag compositions
US20120010331A1